Prolonged mechanical ventilation as a consequence of acute illness. Issue 3 (1st March 1998) - Fraser, J; Henrichsen, T; Mok, Q; Tasker, R C
Abstract : OBJECTIVE: To determine why acutely ill children become dependent upon mechanical ventilation and what happens to them. METHODS: A retrospective medical record study of all patients aged between 1 month and 16 years from 1983 to 1996 who required ventilation for more than 28 days. RESULTS: Forty children were ventilated for between 36 and 180 days before discharge or death. Before their presenting illness, 13 (33%) were normal, 15 (37%) had documented predisposing conditions such as bronchopulmonary dysplasia, and the remaining 12 (30%) had diagnoses made after admission. The cause of respiratory failure was central in four patients (10%), spinal cord in eight (20%), neuromuscular in 11 (28%), and pulmonary in 17 (42%). Severe nosocomial infection requiring treatment with intravenous antibiotics occurred in 22. To date, 16 children (40%) have died, and 10 (25%) remain ventilator dependent. Of the 24 survivors, seven (29%) have severe residual neurological deficit. CONCLUSIONS: Increasingly, children are surviving intensive care only to remain ventilator dependent and at risk of significant comorbidity. This study should inform further debate on why such children remain ventilator dependent, and how and where they are managed.